Changes in tear cytokine and lactoferrin levels in postmenopausal women with primary acquired nasolacrimal duct obstruction complicated with obstructed meibomian gland dysfunction - Haili Jin; Xianjie Chen; Feng Ji; Yin Liu; Yonghong Sheng; Guoping Wang; Linfeng Han; Xiaohu Wang; He Ding; Jing Liu; Qingqing Fu (BMC Ophthalmology)
Abstract Background Epiphora and secondary ocular surface damage are increasingly impairing the quality of life of people, particularly elderly women. We aimed to investigate the changes in tear cytokine and lactoferrin levels in postmenopausal women with primary acquired nasolacrimal duct obstruction (PANDO) complicated with obstructed meibomian gland dysfunction (OMGD) and preliminary explore the pathological mechanisms of OMGD in patients with PANDO. Methods The prospective study involved 43 and 41 postmenopausal women with and without PANDO, respectively. Based on the presence or absence of OMGD, the participants were subdivided. Tear fluid was collected from affected eyes of all participants using Schirmer I test and tested for cytokine concentrations (interleukin (IL)-6, IL-8, IL-1β, interferon-gamma, tumour necrotic factor (TNF)-α, IL-10, epidermal growth factor (EGF)) using the Multiplex Luminex Assay. Tear lactoferrin levels was determined using ELISA. Results In the PANDO with OMGD group, the IL-8, IL-1α, IL-1β, and macrophage inflammatory protein-1α levels were significantly higher than those in the other groups. The IL-6 and TNF-α levels were significantly higher than those in the controls. The lactoferrin level in the PANDO with OMGD group was lower than that in the Non-PANDO with OMGD group. The IL-10 and EGF levels were not significantly different among the groups. Conclusion The level of pro-inflammatory factors in the tears of patients with PANDO complicated with OMGD was significantly increased, which is likely to cause further damage to ocular surface. Anti-inflammatory therapy may help protect ocular surface in postmenopausal women with PANDO.